1997
DOI: 10.1111/j.1365-2869.1997.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Work hours, sleep patterns and fatigue among merchant marine personnel

Abstract: SUMMARY A field study ofwork and sleep patterns among commercial merchant marine personnel is reported. Data collected over a 10-30-d period from 141 subjects aboard eight ships included information concerning work-rest schedules, sleep timing, alertness on the job and critical fatigue. The data indicate that watchstanders on the 4-on, 8-off schedule show considerable disruption in their sleep. The average sleep duration for all mariners is 6.6 h; watchstanders obtain their sleep in fragmented periods that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 6 publications
4
24
0
1
Order By: Relevance
“…Analysis of variance (ANOVA) with simple posthoc comparisons was then conducted to assess differences between rosters and between crews within rosters. In this analysis, it is acknowledged that sleep measures differed between studies, with two studies using PSG (29,39), four studies using actigraphy (22,26,30,36) and the remaining studies using sleep diaries (17,28,32,33,44).…”
Section: Comparing Lwsw Schedulesmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis of variance (ANOVA) with simple posthoc comparisons was then conducted to assess differences between rosters and between crews within rosters. In this analysis, it is acknowledged that sleep measures differed between studies, with two studies using PSG (29,39), four studies using actigraphy (22,26,30,36) and the remaining studies using sleep diaries (17,28,32,33,44).…”
Section: Comparing Lwsw Schedulesmentioning
confidence: 99%
“…Second, sleep duration was related to the quality of LWSW sleep environment (eg, ship cabins, submarine bunks, mining "dongas" and train sleeping wagons). Underlying the importance of environmental factors for optimizing sleep, most studies reported that sleep length was shorter on operations compared to either home or layover (22,25,29,32,36,45). In their large (N=362) survey of offshore fleet workers, Hansen et al (34) found the most frequently endorsed problems when sleeping at sea were noise (55%), cabin vibration (34%), cabin temperature/humidity (30%), alarms (29%), and poor bedding (21%), all of which were more highly ranked than "bothered by shift work" (18%).…”
Section: Narrative Reviewmentioning
confidence: 99%
See 3 more Smart Citations